Respuesta :

"first principle" means "use the limit definition of the derivative":

[tex]f'(x) = \displaystyle \lim_{h\to0} \frac{f(x+h) - f(x)}h[/tex]

For f(x) = y = ax² + b, the derivative is

[tex]f'(x) = \displaystyle \lim_{h\to0} \frac{(a(x+h)^2+b) - (ax^2+b)}h[/tex]

[tex]f'(x) = \displaystyle \lim_{h\to0} \frac{a(x^2+2xh+h^2) - ax^2}h[/tex]

[tex]f'(x) = \displaystyle \lim_{h\to0} \frac{2axh+ah^2}h[/tex]

[tex]f'(x) = \displaystyle \lim_{h\to0} (2ax+ah) = \boxed{2ax}[/tex]

We are given with a function y = ax² + b and are asked to find it's derivative by first principle of differentiation , so by first principle we know that :-

  • [tex]{\boxed{\displaystyle \bf f^{\prime}(x)=\lim_{h\to 0}\dfrac{f(x+h)-f(x)}{h}}}[/tex]

Now , here f(x) is y = ax² + b , so , f(x+h) will be a(x+h)²+b . Now by first principle ;

[tex]{:\implies \quad \displaystyle \sf y^{\prime}=\lim_{h\to 0}\dfrac{\{a(x+h)^{2}+b\}-(ax^{2}+b)}{h}}[/tex]

[tex]{:\implies \quad \displaystyle \sf y^{\prime}=\lim_{h\to 0}\dfrac{\{a(x^{2}+h^{2}+2xh)+b\}-(ax^{2}+b)}{h}\quad \qquad \{\because (a+b)^{2}=a^{2}+b^{2}+2ab\}}[/tex]

[tex]{:\implies \quad \displaystyle \sf y^{\prime}=\lim_{h\to 0}\dfrac{\cancel{ax^{2}}+ah^{2}+2axh+\cancel{b}-\cancel{ax^{2}}-\cancel{b}}{h}}[/tex]

[tex]{:\implies \quad \displaystyle \sf y^{\prime}=\lim_{h\to 0}\dfrac{\cancel{h}(ah+2ax)}{\cancel{h}}}[/tex]

[tex]{:\implies \quad \displaystyle \sf y^{\prime}=a\times 0+2ax}[/tex]

[tex]{:\implies \quad \bf \therefore \quad \underline{\underline{y^{\prime}=2ax}}}[/tex]